Software architecture hour. (O'Reilly Media, Inc., 2021)
Join us for a special conversation on domain-driven design with Neal Ford and Honeycomb principal developer evangelist Jessica Kerr. They'll discuss why domain-driven design is crucial to writing good software and explain how to apply the core principles of domain-driven design beyond just writing software, helping everyone who interacts with your architecture and application. What you'll learn and how you can apply it Learn the benefits of domain-driven design See what's coming next with software architecture This recording of a live event is for you because... You want the chance to ask Neal Ford and Jessica Kerr your questions about how domain-driven design can help you design better systems. You want to better understand how domain-driven design will impact your business architecture. Recommended follow-up: Read (early release book) Learning Domain-Driven Design Watch (recorded event) Software Architecture Superstream Series: Domain-Driven Design and Event-Driven Architecture View (video) Domain-Driven Design Distilled Read (book) Patterns, Principles, and Practices of Domain-Driven Design Take Domain-Driven Design First Steps (live online training course with Andrew Harmel-Law).